Exports, Imports, Domestic Output, and Employment - Leontief, W. W. (Quarterly Journal of Economics, 1946)
I. Relation between the effects of foreign trade and the structural characteristics of the national economy, 171. — Allocation of imports, 172. — Relation between "ultimate" demand and derived output and employment, 174. — Exports as an independent variable, 175. — Dependent and secondary exports, 177. — II. Formulation in precise quantitative terms, 178. — III. Relation between exports and employment in the United States in 1939: entire exports as part of final demand, including household consumption and domestic investment, 184; demand for consumers' goods not independent, 185; net terms of trade allowed for, 186. — General observations, 186.